Patient Safety and Pro Re Nata Prescription and Administration: A Systematic Review - Mojtaba Vaismoradi; Sara Amaniyan; Sue Jordan (MDPI AG, 2018)
PRN is the acronym for ‘pro re nata,’ written against prescriptions whose administration should be based on patients’ needs, rather than at set times. The aim of this systematic review was to explore safety issues and adverse events arising from PRN prescription and administration. Electronic databases including Scopus, PubMed [including Medline], Embase, Cinahl, Web of Science and ProQuest were systematically searched to retrieve articles published from 2005 to 2017. Selection criteria: we included all randomized controlled trials (RCTs) and studies with comparison groups, comparing PRN prescription and administration with scheduled administration, where safety issues and adverse events were reported. The authors independently assessed titles, abstracts and full-texts of retrieved studies based on inclusion criteria and risk of bias. Results were summarised narratively. The search identified 7699 articles. Title, abstract and full-text appraisals yielded 5 articles. The included studies were RCTs with one exception, a pre-test post-test experimental design. Patient populations, interventions and outcomes varied. Studies compared patient-controlled or routine administration with PRN and one trial assessed the effect of a practice guideline on implementation of PRN administration. More analgesia was administered in the patient-controlled than the PRN arms but pain reduction was similar. However, there was little difference in administration of psychotropic medicines. No differences between patient-controlled and PRN groups were reported for adverse events. The PRN practice guideline improved PRN patient education but non-documentation of PRN administration increased. This systematic review suggests that PRN safety issues and adverse events are an under-researched area of healthcare practice. Variations in the interventions, outcomes and clinical areas make it difficult to judge the overall quality of the evidence. Well-designed RCTs are needed to identify any safety issues and adverse events associated with PRN administration.